Caracterización Geológica-Geotécnica del barrio San José de las Peñas, parroquia Malacatos, cantón y provincia de Loja - Cuenca Gordillo, Carlos Alejandro (2023)
The purpose of this investigation was to carry out the "Geotechnical Geological Characterization of San José de las Peñas neighborhood, Malacatos parish, canton and province of Loja. The work began with the topographic survey at a scale of 1:2500, which served as the basis for carrying out the geological survey where intercalations of shale, clay, sandstone and plaster sheets corresponding to the San Francisco formation were found; Metamorphic and volcanic clasts with a sandy-clay matrix belonging to the Miocene San José formation, as well as colluvial deposits of the sandstone and clay type with small clasts of different origin corresponding to the neighboring Quaternary formations. Within the geotechnical campaign, direct and indirect methods were applied, such as Standard Penetration Tests (SPT's) and vertical electrical soundings (VES´s). For the direct methods, a total of 5 SPT's were carried out, distributed within the different lithologies found in the geological characterization, from the samples obtained, tests were conducted in the ESTSUELCON soils laboratory according to ASTM standards, such as: granulometry, moisture content, Atterberg limits, and AASTHO and SUCS classifications. Regarding indirect methods, 5 VES's tests were performed at the same points where the SPT's were obtained; These allowed us to know the different layers of the subsoil and correlate them with tables of geomaterials proposed by other researchs, thus obtaining the soil map that served as a basis along with the geology, moisture content, behavior of clays, admissible load, topography and slope to obtain the geological geotechnical zoning map of San José de las Peñas neighborhood. With the results obtained in this investigation, some mitigation measures are recommended, such as: drainage or channeling of surface water, replacement of collapsed traditional septic tanks by biodigester tanks, and it is also recommended that residents request technical advice when designing new infrastructures. Keywords: topography, photointerpretation, geology, geotechnical characterization